Prevalence of transformable Streptococcus mutans in human dental plaque. - Westergren, G (1983)
A total of 100 strains of Streptococcus mutans serotypes c/e/f and d/g, freshly isolated from dental plaque, were screened for their ability to undergo genetic transformation to streptomycin resistance. Of the serotype c/e/f strains, 28% were found to be transformable, whereas none of the serotype d/g strains could be transformed by donor DNA from streptomycin-resistant S. mutans strains of either serotype c or d/g. Two of the transformable serotype c/e/f strains were transformed by DNAs from a variety of oral streptococcal species commonly found in the microflora.